Utilization of Constitutive Elements in Unjust Legal Actions - Liu, Xinyu; Li, Pengling (Pacific International Journal, 2024)
The system that deals with unfairness in civil transactions in China has been continuously improved as a result of the dynamic nature of the market economy. The objective is to deter inequitable conditions and transactions in civil exchanges, guaranteeing that contractual parties participate in commerce founded on principles of equity and free will. This paper examines the fundamental components of unjust legal actions as outlined in the Chinese Civil Code. It investigates how these elements are applied and evolved in legal practice, and draws comparisons with similar legal systems worldwide, particularly the approaches taken in Germany and France. The aim is to offer insights that can contribute to enhancing the Chinese legal system. Hence, the study suggests practical uses for the fundamental components of unjust legal activities, such as improving the objective factors, broadening the subjective factors, and incorporating the dynamic system theory to tackle identification challenges in the field of judiciary. The suggestions propose the creation of a precise and adaptable legal framework to quantify unequal exchanges and consider transactional backgrounds as objective factors. They also recommend expanding three subjective elements: "a notable deficiency in the determination of the party", "manipulation by the party in power" and "violation of the genuine intention of the party". Additionally, they suggest managing the relationship between the constitutive conditions of unfairness in a flexible manner based on the specific circumstances of each case. These measures aim to achieve judicial fairness and improve judicial efficiency.